How do we know we are doing good work? - Sharp, Cathy; McLaughlin, Dot; Whitley, Janet; Lawson, Karen (Collective Leadership for Scotland, 2022)
Collective leadership feels timely and important in an uncertain, fast changing, and challenging world. This report comes at this heightened moment of urgency and appetite for renewal, bringing potential to do things differently in public services and communities. The opportuniti es and challenges of true collaboration-in-practice, in the absence of blueprints, mean that it has never been more necessary to change ways of working and foreground learning. As outcomes remain important, and time and resources are scarcer than ever, the approach of collective leadership makes the creation of impact a shared, conscious, and actio nable choice. A pathway to ultimate impact at scale is co-created thro ugh dialogue about expectations and contributions, and by design, not assuming change will happen because we have good intentions. Collectiv e Leadership for Scotland (CLfS) has a strong vision and enjoys contin uing active interest, drawing together participants from a variety of agencies working in public services. People are looking for fresh thin king, space and time for reflection, connection with others, a chance to think about how to tackle difficulties, and to test out what it tak es to do, and continue to do, the work of collaborative public service . These motivations are deepened and brought into sharper focus by the pandemic, with an added interest in developing skills in online facil itation. CLfS contributes to building a critical mass for system chang e, to help to sustain the ambitions of the Christie Commission and the delivery of the National Outcomes for Scotland. There remains further potential to realise wider and deeper impact amongst organisations, c ommunities, and wider systems. The conclusions of this report are like ly to have wider resonance beyond interests in the CLfS programmes. Th is report deepens understanding of some of the challenges of commissio ning, convening, and the scope for deeper impact through building refl ective and relational leadership practices. It also outlines social an d experiential sensemaking and facilitation practices to strengthen th e action inquiry approach as a deliberate learning strategy, building cultures that support new forms of collaborative inquiry and systemic action research.